Improving Fishermen's Capacity and Skills Through a Pilot Boat Workshop in Karangharjo Village, Rembang Regency - Maulana, Sonika; Saputro, Danang Dwi; Suseno, Deky Aji (Universitas Negeri Semarang, 2025)
The community service programme in Karangharjo Village, Rembang Regency, was implemented through a pilot workshop on ship repair as an effort to improve the capacity and technical skills of coastal fishermen. The main problems faced by local fishermen were a lack of understanding of ship diesel engine maintenance, limited access to repair workshops, and the use of manual techniques that risked engine damage. This community service activity was designed with a group-based approach, local potential, and comprehensive intervention, including training in engine maintenance and repair, practical use of workshop equipment, tool management inventory, and the construction of a community-based shipyard workshop. The results of the activity showed an increase in fishermen's skills in performing routine maintenance, managing workshop equipment, and readiness to manage workshops independently. This programme supports the achievement of the Sustainable Development Goals (SDGs), particularly SDG 1 (No Poverty), SDG 8 (Decent Work and Economic Growth), SDG 9 (Industry, Innovation and Infrastructure), and SDG 14 (Life Below Water). With the establishment of synergy between universities, village governments, and fishermen's groups, this workshop initiative is expected to increase the independence, business sustainability, and economic resilience of coastal communities.